(untitled) (Conferencea, 2022)
This article analyzes the results of Archaeological Research in and around the city of Tashkent. As a result of the penetration of Russian Orientalists into the territory of Turkestan, first of all, local material culture was studied and many historical sources were studied, then gradually the first steps were also taken to archaeological research.